Comparison of Pipelined Floating Point Unit with Unpipelined Floating Point Unit - M. Venkateswarao; J. Triveni; K. Bhargavee Latha; K. Naga Deepika; K.R. Pavan (Universitas Islam Sultan Agung, 2015)
Floating-point numbers are broadly received in numerous applications due their element representation abilities. Floating-point representation has the capacity hold its determination and exactness contrasted with altered point representations. Any Digital Signal Processing (DSP) calculations utilization floating-point math, which obliges a huge number of figuring’s every second to be performed. For such stringent necessities, outline of quick, exact and effective circuits is the objective of each VLSI creator. This paper displays a correlation of pipelined floating-point snake dissention with IEEE 754 organization with an unpipelined viper additionally protests with IEEE 754 arrangement. It depicts the IEEE floating-point standard 754. A pipelined floating point unit in light of IEEE 754 configuration is produced and the outline is contrasted and that of an unpipelined floating point unit and an investigation is defeated speed, range, and force contemplations. It builds the rate as well as is vitality productive. Every one of these changes is at the expense of slight increment in the chip region. The basic methodology and approach used for VHDL (Very Large Scale Integration Hardware Descriptive Language) implementation of the floating-point unit are also described. Detailed synthesis report operated upon Xilinx ISE 11 software and Modelsim is given.